Liposomes produced by reverse phase evaporation: In vitro and in vivo efficacy of diminazene aceturate against Trypanosoma evansi - Oliveira C.B. (2014)
This study aimed to develop and test the in vitro and in vivo effectiveness of diminazene aceturate encapsulated into liposomes (L-DMZ) on Trypanosoma evansi. To validate the in vitro tests with L-DMZ, the efficacy of a commercial formulation of diminazene aceturate (C-DMZ) was also assessed. The tests were carried out in culture medium for T. evansi, at concentrations of 0·25, 0·5, 1, 2 and 3μgmL-1 of L-DMZ and C-DMZ. A dose-dependent effect was observed for both formulations (L-DMZ and C-DMZ), with the highest dose-dependent mortality of trypomastigotes being observed at 1 and 3h after the onset of tests with L-DMZ. The results of in vivo tests showed the same effects in the animals treated with L-DMZ and C-DMZ in single doses of 3·5mgkg-1 and for 5 consecutive days (3·5mgkg -1day-1). It was possible to conclude that T. evansi showed greater in vitro susceptibility to L-DMZ when compared with C-DMZ. In vivo tests suggest that treatment with the L-DMZ and C-DMZ showed similar efficacy in vivo. The potential of the formulation developed in this study was clearly demonstrated, as it increased the efficacy of the treatment against trypanosomosis, but more studies are needed to increase the effectiveness in vivo. © 2014 Cambridge University Press.